Advanced Intelligent Systems for Sustainable Development (AI2SD'2018) Vol 2: Advanced Intelligent Systems Applied to Energy - Ezziyyani, Mostafa (Advances in Intelligent Systems and Computing,, 2019)
This book gathers papers presented at the International Conference on Advanced Intelligent Systems for Sustainable Development (AI2SD-2018), which was held in Tangiers, Morocco on 12-14 July 2018. In addition to the latest research in the field of energy, it offers new solutions, tools and effective techniques, and provides essential information on smart grids, renewable and economical energy. Further, it addresses modeling, storage management and decision support in the field of energy, offering a valuable guide for researchers, professionals and all those who are interested in the development of advanced intelligent systems in the energy sector.